Id's Model in the Leadership of Muhammadiyah Principals - Samroji, Odjie (Green Publisher Indonesia, 2025)
This study unveils the essence of Muhammadiyah principals’lived experiences in enacting imaginativeness, decisiveness, and sociability. Despite extensive research on transformational leadership in Islamic education, a critical knowledge gap exists regarding how these three competencies synergistically operate within the unique cultural-religious context of Indonesian Muhammadiyah schools. The theoretical novelty of this study lies in proposing the IDS Triadic Model, which integrates transformational, ethical, and relational leadership paradigms into a unified framework grounded in Islamic values. Adopting Moustakas’ transcendental phenomenology, data were gathered from in-depth interviews, participant observations, and document analysis with six junior/senior high school principals in Yogyakarta. Analysis followed epoché/bracketing, horizontalization, clustering of meaning units, textural–structural descriptions, and synthesis of essences. Findings suggest an Islamic transformational pattern that integrates creative, value-driven vision, morally anchored yet non-authoritarian decisiveness, and Ukhuwah-based human relations. The paper proposes the IDS Triadic Model and nine actionable practices.